Relevansi Gereja Kontemporer : Kajian Teologi Sistematika tentang Visibilitas dan Invisibilitas (International Forum of Researchers and Lecturers, 2025)
This article explores the relevance of the contemporary church through the lens of systematic theology by examining the concepts of visibility (the church’s tangible presence) and invisibility (its spiritual and unseen essence). The topic is crucial as many churches today face a tension between their social engagement and their spiritual identity. The central issue addressed in this research is how the church can maintain its theological integrity while remaining visibly active and impactful in an ever-changing society. This study employs a qualitative method using a literature review approach, analyzing theological texts, academic articles, and biblical references to investigate ecclesiological perspectives on integrating visibility and invisibility. The data is analyzed descriptively and reflectively to identify theological patterns and practical implications for the life of the church today. The findings reveal that a relevant church is one that successfully integrates both visible and invisible dimensions. Visibility is essential for contextual engagement with the world, while invisibility sustains spiritual depth and fidelity to Christ. This integration results in a church that is actively present in society, while also rooted in holiness, love, and prophetic mission. The study recommends that churches engage in theological reflection to reassess their identity and ministry to remain relevant without losing their spiritual direction.